Glass articles having adhesive beads with controlled angle at glass-adhesive interface and related methods
By designing adhesive beads with an angle of 35° to 60° between the glass substrate and the support structure, the problem of stress singularity between the glass substrate and the frame system in the vehicle is solved, and the bonding strength and the service life of the parts are improved. .
Patent Information
- Application Number
- CN202380049616.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-07
- Filing Date
- 2023-06-22
- Publication Date
- 2025-02-11
AI Technical Summary
Between the glass substrate inside the vehicle and the frame system, stress singularity leads to instability in the strength of the adhesive, affecting the service life of the parts.
A glass article is designed, including a support structure, a glass substrate and adhesive beads. The outer surface of the adhesive bead extends between the glass substrate and the support structure, with an extension angle greater than or equal to 35° and less than or equal to 60° to reduce stress singularity.
By reducing stress singularity, the bonding strength between the glass substrate and the frame system is improved, and the stability and service life of the parts are enhanced.
Smart Images

Figure CN119421864A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority under the U.S. Patent Application No. 63 / 359,020, filed on July 7, 2022, which is incorporated herein by reference in its entirety. Technical Field
[0003] The present disclosure relates to glass articles for vehicle interior systems, and more particularly to a glass article having angled adhesive beads at the glass-adhesive interface and the frame-adhesive interface to reduce or even suppress stress singularities in the presence of various loads for improved assembly strength. Background Art
[0004] Vehicle interiors may incorporate glass substrates as part of the aesthetic and functional design of the vehicle. Such glass substrates may be bonded to a frame system that attaches the glass surface to the vehicle interior. The glass substrate may be bonded by the frame system by a suitable adhesive. This adhesive may be subject to stress throughout the service life of the vehicle interior. For example, the frame and glass substrate may be composed of different materials with different thermal expansion properties, which may induce stress in the adhesive when the temperature changes. In another example, the glass substrate may be cold formed to conform to the shape of the frame, resulting in continuous bending-induced stress in the adhesive.
[0005] Given the presence of such stresses in vehicle interior components that incorporate glass substrates, a robust estimate of bond strength is needed. Certain existing designs incorporate adhesive bead structures that induce stress singularities at the glass-frame interface in various finite element models that can be used to predict bond stresses. Such stress singularities make the evaluation of modeling results very difficult, potentially leading to unreliable designs that are prone to delamination over the life of the part.
[0006] Therefore, there is a need for an adhesive bead structure that helps reduce such stress singularities to enable more reliable part designs that incorporate glass substrates. Summary of the invention
[0007] Therefore, there is a need for an adhesive bead structure that helps reduce such stress singularities to enable more reliable part designs that incorporate glass substrates.
[0008] Aspect (1) of the present disclosure relates to a glass product, comprising: a support structure comprising a support surface; a glass substrate comprising a first major surface and a second major surface, the second major surface being opposite to the first major surface; and an adhesive bead disposed between the support surface and the second major surface, wherein: the adhesive bead comprises a plurality of outer surfaces extending between the support structure and the glass substrate, the plurality of outer surfaces extending at a first angle relative to the second major surface at a first edge thereof closest to the glass substrate, and each of the first angles is greater than or equal to 35° and less than or equal to 60°.
[0009] Aspect (2) of the present disclosure relates to the glass article according to aspect (1), wherein the plurality of outer surfaces extend at a second angle relative to the support surface at a second edge thereof closest to the support structure.
[0010] Aspect (3) of the present disclosure relates to the glass article according to aspect (2), wherein for each of the plurality of exterior surfaces, the first angle is equal to the second angle.
[0011] Aspect (4) of the present disclosure relates to the glass article according to any one of aspects (1) to (3), wherein each of the first angles is greater than or equal to 40° and less than or equal to 50°.
[0012] Aspect (5) of the present disclosure relates to the glass article according to any one of aspects (1) to (4), wherein each of the first angles is greater than or equal to 42° and less than or equal to 48°.
[0013] Aspect (6) of the present disclosure relates to the glass article according to any one of aspects (1) to (5), wherein each of the first angles is greater than or equal to 44° and less than or equal to 46°.
[0014] Aspect (7) of the present disclosure relates to the glass article according to any one of aspects (1) to (6), wherein the support surface is curved, and when the glass substrate is cold formed, the adhesive beads hold the glass substrate on the support surface in the curved configuration.
[0015] Aspect (8) of the present disclosure relates to a glass article according to aspect (7), wherein: as the glass substrate is cold formed, the adhesive bead is maintained in a tensile stress state, and a position where the tensile stress in the adhesive bead includes a maximum magnitude is displaced from an interface between the adhesive bead and the glass substrate and displaced to a bulk of the adhesive bead.
[0016] Aspect (9) of the present disclosure relates to the glass article according to any one of aspects (1) to (8), wherein the adhesive bead extends continuously around the periphery of the glass substrate between the glass substrate and the support structure.
[0017] Aspect (10) of the present disclosure relates to a glass article according to any one of aspects (1)-(8), wherein the glass article includes a plurality of adhesive beads arranged along a bead path between a glass substrate and a support structure, each of the plurality of adhesive beads including a plurality of outer surfaces, the plurality of outer surfaces extending at a first angle relative to the second major surface, the first angle being greater than or equal to 35° and less than or equal to 60°.
[0018] Aspect (11) of the present disclosure relates to the glass article according to any one of aspects (1)-(10), wherein the plurality of outer surfaces of the adhesive bead are concave such that the adhesive bead comprises a minimum cross-sectional dimension between the glass substrate and the support structure.
[0019] Aspect (12) of the present disclosure relates to the glass article according to aspect (11), wherein each of the plurality of outer surfaces of the adhesive bead is continuously curved over the entire distance between the glass substrate and the support structure.
[0020] Aspect (13) of the present disclosure relates to the glass article according to any one of aspects (1) to (12), wherein the adhesive beads include an elastic modulus of 0.1 MPa to 300 MPa in a cured state.
[0021] Aspect (14) of the present disclosure relates to a glass product, comprising: a support structure comprising a curved support surface, the curved support surface being curved with a radius of curvature greater than or equal to 75 mm and less than or equal to 10,000 mm; a glass substrate comprising a first major surface and a second major surface, the second major surface being opposite to the first major surface; and an adhesive bead, the adhesive bead being disposed between the curved support surface and the second major surface and holding the glass substrate in a curved shape on the curved support surface, wherein: the glass substrate is cold formed so that stress exists in the adhesive bead, the adhesive bead comprising a plurality of outer surfaces extending between the support structure and the glass substrate, the plurality of outer surfaces extending at a first angle relative to the second major surface at a first edge thereof closest to the glass substrate, and each of the first angles being greater than or equal to 35° and less than or equal to 60°, so that a position at which stress in the adhesive bead is at a maximum is displaced from an interface between the glass substrate and the adhesive bead.
[0022] Aspect (15) of the present disclosure relates to the glass article according to aspect (14), wherein the plurality of outer surfaces extend at a second angle relative to the support surface at a second edge thereof closest to the support structure.
[0023] Aspect (16) of the present disclosure relates to the glass article according to aspect (15), wherein for each of the plurality of exterior surfaces, the first angle is equal to the second angle.
[0024] Aspect (17) of the present disclosure relates to the glass article according to any one of aspects (14) to (16), wherein each of the first angles is greater than or equal to 40° and less than or equal to 50°.
[0025] Aspect (18) of the present disclosure relates to the glass article according to any one of aspects (14)-(17), wherein each of the first angles is greater than or equal to 44° and less than or equal to 46°.
[0026] Aspect (19) of the present disclosure relates to the glass article according to any one of aspects (14) to (18), wherein the adhesive bead extends continuously around the periphery of the glass substrate between the glass substrate and the support structure.
[0027] Aspect (20) of the present disclosure relates to a glass article according to any one of aspects (14)-(18), wherein the glass article includes a plurality of adhesive beads arranged along a bead path between a glass substrate and a support structure, each of the plurality of adhesive beads including a plurality of outer surfaces, the plurality of outer surfaces extending at a first angle relative to the second major surface, the first angle being greater than or equal to 35° and less than or equal to 60°.
[0028] Aspect (21) of the present disclosure relates to a glass article according to any one of aspects (14)-(20), wherein multiple outer surfaces of the adhesive bead are concave such that the adhesive bead includes a minimum cross-sectional dimension between the glass substrate and the support structure.
[0029] Aspect (22) of the present disclosure relates to a glass article according to any one of aspects (14) to (21), wherein: the adhesive beads comprise an elastic modulus of 0.1 MPa to 300 MPa in a cured state, and the support structure is composed of one of aluminum and stainless steel.
[0030] Aspect (23) of the present disclosure relates to a method for attaching a glass substrate to a supporting structure, the method comprising: dispensing an adhesive bead on one of a glass substrate and a supporting structure when the adhesive of the adhesive bead is in an uncured state; contacting the adhesive bead with a plurality of shaping members to shape an outer surface of the adhesive bead so that the outer surface of the adhesive bead extends at an angle greater than or equal to 35° and less than or equal to 60° relative to one of the glass substrate and the supporting structure at an edge of the outer surface; contacting a plurality of shaping members with the other of the glass substrate and the supporting structure so that after shaping, the adhesive bead contacts both the supporting structure and the glass substrate; and curing the adhesive to solidify the adhesive bead so that the glass substrate and the supporting structure are bonded to each other through the adhesive bead.
[0031] Aspect (24) of the present disclosure relates to the method according to aspect (23), wherein bringing the adhesive bead into contact with the plurality of shaping members comprises: after dispensing the adhesive bead, moving the plurality of shaping members into contact with the adhesive bead.
[0032] Aspect (25) of the present disclosure relates to a method according to aspect (24), wherein the plurality of shaping members are moved to contact the adhesive beads by placing the plurality of shaping members between the glass substrate and the support structure so that the shaping members are in contact with the glass substrate and the support structure.
[0033] Aspect (26) of the present disclosure relates to a method according to aspect (23), wherein contacting the adhesive beads with a plurality of shaping members comprises: dispensing the adhesive into an adhesive shaping cavity defined by a plurality of sacrificial shaping members disposed on one of the glass substrate and the support structure.
[0034] Aspect (27) of the present disclosure relates to the method according to aspect (26), further comprising: removing the plurality of sacrificial shaping members after curing of the adhesive, so that the adhesive bead retains a shape determined by the plurality of sacrificial shaping members.
[0035] Aspect (28) of the present disclosure relates to the method according to aspect (27), wherein the plurality of sacrificial plastic components are formed of a wax material, and removing the plurality of sacrificial plastic components includes heating the plurality of sacrificial plastic components to a temperature less than or equal to 70°C.
[0036] Aspect (29) of the present disclosure relates to the method according to any one of aspects (23) to (28), the method further comprising: cold forming the glass substrate by applying a bending force to the glass substrate before depositing the adhesive.
[0037] Aspect (30) of the present disclosure relates to a method according to aspect (29), wherein the adhesive is dispensed on the glass substrate after cold forming, and after the adhesive is cured, the adhesive bead holds the glass substrate in a cold formed state such that bending stress exists in the adhesive bead.
[0038] Aspect (31) of the present disclosure relates to a method according to any one of aspects (23)-(30), wherein the outer surface of the adhesive bead extends at a certain angle relative to both the glass substrate and the supporting structure at its edge due to being contacted by multiple shaping members, and the angle is greater than or equal to 35° and less than or equal to 60°.
[0039] It is to be understood that both the foregoing general description and the following detailed description are merely exemplary and are intended to provide an overview or framework for understanding the nature and character of the claims. The accompanying drawings are included to provide a further understanding, and are incorporated in and constitute a part of this specification. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several aspects of the present invention and, together with the description, serve to explain the principles of the invention. In the drawings:
[0041] Figure 1 is a perspective view of a vehicle interior having a curved glass surface according to one or more embodiments of the present disclosure;
[0042] Figure 2A and Figure 2B Describes a method that can be used in accordance with one or more embodiments of the present disclosure. Figure 1 A side view of an embodiment of a curved glass article for use in a vehicle interior;
[0043] Figure 3 depicts an embodiment of a cold forming arrangement for producing a glass article in accordance with one or more embodiments of the present disclosure;
[0044] Figure 4 schematically depicts a side view of a glass-adhesive interface according to one or more embodiments of the present disclosure;
[0045] Figure 5A depicts an adhesive bead according to one or more embodiments of the present disclosure having stresses thereon modeled using a finite element model;
[0046] Figure 5B is to draw a close Figure 5A Plot of stress at the integration point of the corners of the adhesive bead depicted in , as a function of the mesh size used in the finite element model;
[0047] Fig. 6A is a graph plotting the order of stress singularities at corners of an adhesive bead according to one or more embodiments of the present disclosure as a function of the angle at which the outer surface of the adhesive extends relative to the glass at the glass-adhesive interface, as predicted using analytical calculation methods;
[0048] Figure 6B is a graph plotting the order of stress singularities at corners of an adhesive bead as a function of the angle at which the outer surface of the adhesive extends relative to the glass at the glass-adhesive interface, predicted for open (Mode I) and sliding (Mode II) failure modes using a finite element model, in accordance with one or more embodiments of the present disclosure;
[0049] Figure 7A-1 and Figure 7A-2 depicting a plurality of images of a plurality of adhesive beads having edges extending at different angles relative to a glass substrate when simulated to be subjected to shear stress in accordance with one or more embodiments of the present disclosure;
[0050] Figure 7B-1 and Figure 7B-2 depicting a plurality of images of a plurality of adhesive beads having edges extending at different angles relative to a glass substrate when simulated to be subjected to a tensile stress in accordance with one or more embodiments of the present disclosure;
[0051] Fig. 8A depicts a simulated adhesive bead having a straight edge design when subjected to shear stress associated with an open failure mode in accordance with one or more embodiments of the present disclosure;
[0052] Figure 8B depicts a simulated adhesive bead having a concave edge design when subjected to shear stress associated with an open failure mode in accordance with one or more embodiments of the present disclosure;
[0053] Figure 8C depicts a simulated adhesive bead having a straight edge design when subjected to shear stress associated with a sliding failure mode in accordance with one or more embodiments of the present disclosure;
[0054] Fig.8D depicts a simulated adhesive bead having a concave edge design when subjected to shear stress associated with a sliding failure mode in accordance with one or more embodiments of the present disclosure;
[0055] Fig.9A depicts a simulated adhesive bead having a straight edge design when subjected to a tensile stress associated with an open failure mode in accordance with one or more embodiments of the present disclosure;
[0056] Fig. 9B depicts a simulated adhesive bead having a concave edge design when subjected to a tensile stress associated with an open failure mode in accordance with one or more embodiments of the present disclosure;
[0057] Fig. 9C depicts a simulated adhesive bead having a straight edge design when subjected to a tensile stress associated with a sliding failure mode in accordance with one or more embodiments of the present disclosure;
[0058] Fig.9D depicts a simulated adhesive bead having a concave edge design when subjected to a tensile stress associated with a sliding failure mode in accordance with one or more embodiments of the present disclosure;
[0059] Fig. 10A depicts a simulated adhesive bead having a straight edge design when subjected to stress induced by a coefficient of thermal expansion (CTE) mismatch between a glass substrate and a support structure, the stress being associated with an open failure mode, according to one or more embodiments of the present disclosure;
[0060] Fig. 10B depicts a simulated adhesive bead having a concave edge design when subjected to stress induced by a coefficient of thermal expansion (CTE) mismatch between a glass substrate and a support structure, the stress being associated with an open failure mode, according to one or more embodiments of the present disclosure;
[0061] Fig. 10C depicts a simulated adhesive bead having a straight edge design when subjected to stress induced by a coefficient of thermal expansion (CTE) mismatch between a glass substrate and a support structure, the stress being associated with a sliding failure mode, according to one or more embodiments of the present disclosure;
[0062] Fig. 10D depicts a simulated adhesive bead having a concave edge design when subjected to stress induced by a coefficient of thermal expansion (CTE) mismatch between a glass substrate and a support structure, the stress being associated with a sliding failure mode, according to one or more embodiments of the present disclosure;
[0063] Fig.11A schematically illustrates a portion of a glass article during shaping of adhesive beads using a plurality of shaping members according to one or more embodiments of the present disclosure;
[0064] Fig. 11B schematically illustrates a portion of a glass article during shaping of adhesive beads with a plurality of sacrificial shaping members according to one or more embodiments of the present disclosure;
[0065] Fig.12 A flow chart depicting a method of attaching a glass substrate to a support structure using adhesive beads according to one or more embodiments of the present disclosure; and
[0066] Fig.13 A glass substrate according to one or more embodiments of the present disclosure is schematically depicted. DETAILED DESCRIPTION
[0067] Reference will now be made in detail to various embodiments, examples of which are shown in the accompanying drawings. A glass article is disclosed that includes a support structure and a glass substrate connected to each other by an adhesive. The adhesive is formed into an adhesive bead having an outer surface extending between the glass substrate and the support structure. The outer surface extends at a certain angle relative to the surfaces of the glass substrate and the support structure at the interface between the glass substrate and the support structure. The angle is specifically selected to suppress physical stress singularities at the interface between the adhesive, the glass substrate, and the support structure. In an embodiment, the angle at which the outer surface of the adhesive bead extends relative to the glass substrate and the support structure is greater than or equal to 35° and less than or equal to 60° (e.g., greater than or equal to 35° and less than greater than or equal to 50°, greater than or equal to 36° and less than or equal to 50°, greater than or equal to 37° and less than or equal to 50°, greater than or equal to 38° and less than or equal to 50°, greater than or equal to 39° and less than or equal to 50°, greater than or equal to 40° and less than or equal to 50°, greater ... 41° and less than or equal to 50°, greater than or equal to 42° and less than or equal to 50°, greater than or equal to 43° and less than or equal to 49°, greater than or equal to 42° and less than or equal to 48°, greater than or equal to 44° and less than or equal to 48, greater than or equal to 44° and less than or equal to 47°, greater than or equal to 44° and less than or equal to 46°, greater than or equal to 44° and less than or equal to 46°, greater than or equal to 44.5° and less than or equal to 45.5°, about 45°). Such angles at the interface between adhesive, support structure and glass substrate advantageously suppress physical stress singularities, as will become apparent herein, making stress prediction less dependent on finite element analysis grid size, and therefore more reliable. In addition, it has been found that such angles at the interface may reduce the stress concentration associated with various failure modes at the bonding interface. Due to the adhesive bead structure described herein, stress peaks are observed in the bulk of the adhesive, where finite element analysis can be used to accurately predict stress peaks. Due to the adhesive bead structure described herein, the maximum stress associated with various failure modes (e.g., opening, sliding) is also reduced by more than 15%. Therefore, the adhesive bead structure described herein enables the use of adhesives to make more reliable glass parts by reducing stress and making such stress more predictable.
[0068] Also disclosed is an embodiment of a method for manufacturing a glass product, the glass product having an adhesive bead structure, the adhesive bead structure having an outer surface extending at an angle within the above range relative to the surface of the glass substrate and the support structure. The method includes: placing an adhesive bead of an adhesive in an uncured state with a desired volume on one of the glass substrate and the support structure, and placing the support structure and the frame together so that the adhesive bead contacts the support structure and the glass substrate. When the adhesive is in a deformable state (e.g., before the adhesive is fully cured), a shaping member is brought into contact with the adhesive bead. The adhesive in a deformable state conforms to the shape of the shaping member so as to form an outer surface on the periphery of the adhesive bead, the outer surface extending at an angle between 35° and 50° relative to the surface of the support structure and the glass substrate. In an embodiment, the shaping member is a removable gasket with a convex surface, which is brought into contact with the adhesive after the adhesive is dispensed, and is removed once the adhesive is able to maintain the shape imparted thereto by the gasket. In an embodiment, the shaping surface is a surface of a sacrificial material (e.g., wax or other removable material) disposed on one of the glass substrate and the support structure before dispensing the adhesive. The sacrificial material can be removed after the adhesive is fully cured, so that the adhesive acquires the shape imparted by the sacrificial material. Such methods are compatible with adhesives that can be cured at room temperature. Adhesives that cure at temperatures above room temperature can also be used with the sacrificial materials described herein, as long as the adhesive acquires its final shape before melting the sacrificial material.
[0069] Although the examples described herein relate to applications in which a glass substrate is coupled to a support structure using a suitable adhesive, the adhesive interface angles and associated methods described herein may be applied to any adhesive system that uses an adhesive to attach materials having different elastic properties (e.g., in terms of Young's modulus and Poisson's ratio) to each other.
[0070] Figure 1 An exemplary vehicle interior 10 of a vehicle is shown, the vehicle interior including three different embodiments of vehicle interior systems 20, 30, 40. The vehicle interior system 20 includes a base shown as a center console base 22, the base having a curved surface 24 including a display 26. The vehicle interior system 30 includes a base shown as an instrument panel base 32, the base having a curved surface 34 including a display 36. The instrument panel base 32 generally includes an instrument panel 38, which may also include a display. The vehicle interior system 40 includes a base shown as a steering wheel base 42, the base having a curved surface 44 and a display 46. In one or more embodiments, the vehicle interior system includes a base, the base is an armrest, pillar, seat back, floor, headrest, door panel, or any part of the vehicle interior that includes a curved structure. In other embodiments, the base is part of a housing for a freestanding display (i.e., a display that is not permanently attached to a part of the vehicle).
[0071] Embodiments of the curved glass articles described herein may be used in each of the vehicle interior systems 20, 30, 40, etc. In some such embodiments, the glass articles discussed herein may include a cover glass sheet that also covers non-display surfaces of the instrument panel, center console, steering wheel, door panels, etc. In such embodiments, the glass material may be selected based on its weight, aesthetic appearance, etc., and may be provided with a coating (e.g., an ink or pigment coating) with a pattern (e.g., a brushed metal look, a wood grain look, a leather look, a colored look, etc.) to visually match the glass component to an adjacent non-glass component. In particular embodiments, such ink or pigment coatings may have a level of transparency that provides a dead panel or color matching function when the display 26, 36, 46 is inactive. In addition, although Figure 1 The vehicle interior of the present invention depicts a vehicle in the form of an automobile (e.g., a car, truck, bus, etc.), but the glass articles disclosed herein may be incorporated into other vehicles such as trains, watercraft (boats, ships, submarines, etc.) and aircraft (e.g., drones, airplanes, jets, helicopters, etc.).
[0072] In embodiments, displays 26, 36, and 46 are flat and include a cover glass having a flat major surface. In embodiments, one or more of displays 26, 36, and 46 are curved, and the curved display may include a curved cover glass that may be hot-formed or cold-formed to have such a curvature. For example, such embodiments may incorporate adhesive bead structures described herein of adhesive for attaching the curved cover glass to a curved frame or support structure. Such cold forming may involve any of the techniques described in U.S. Pregrant Publication No. 2019 / 0329531A1, entitled “Laminating thin strengthened glass to curved molded plastic surface for decorative and display cover application,” U.S. Pregrant Publication No. 2019 / 0315648A1, entitled “Cold-formed glass article and assembly process thereof,” U.S. Pregrant Publication No. 2019 / 0012033A1, entitled “Vehicle interior systems having a curved cover glass and a display or touch panel and methods for forming the same,” and U.S. Patent Application No. 17 / 214,124, entitled “Curved glass constructions and methods for forming same,” each of which is incorporated herein by reference in its entirety.
[0073] When incorporated into a curved display, such as displays 26, 36, and 46, the glass articles described herein can have a variety of different shapes. For example, Figure 2A and Figure 2B Depicts side views of two embodiments of glass articles 50. Glass articles 50 may be, among other glass articles. Figure 1 Components of any of the displays 26, 36, and 46 depicted in FIG. Figure 2A, showing a side view of an embodiment of a glass article 50 in a V-shaped configuration. The glass article 50 includes a glass substrate 52 having a first major surface 54, a second major surface 56 opposite the first major surface 54, and a minor surface 58 joining the first major surface 54 to the second major surface 56. The first major surface 54 and the second major surface 56 define a thickness T of the glass substrate 52. In an embodiment, the thickness T of the glass substrate 52 is 0.3 mm to 2 mm, specifically 0.5 mm to 1.1 mm. In a vehicle, the first major surface 54 faces an occupant of the vehicle.
[0074] In an embodiment, the first major surface 54 and / or the second major surface 56 include one or more surface treatments. Examples of surface treatments that can be applied to one or both of the first major surface 54 and the second major surface 56 include anti-glare coatings, anti-reflective coatings, coatings that provide touch functionality, decorative (e.g., ink or paint) coatings, and easy-to-clean coatings.
[0075] like Figure 2A As can be seen in FIG. 5 , the glass substrate 52 has a curved region 60 disposed between a first flat section 62a and a second flat section 62b. In an embodiment, the curved region 60 has a radius of curvature R of 75 mm to less than the radius of curvature of a substantially flat or planar surface (e.g., R=10 m). Specifically, the curved region 60 has a radius of curvature R of 150 mm to 3000 mm. In addition, as Figure 2A As shown, the curved region 60 defines a concave curve relative to the first major surface 54 , but in other embodiments, the curved region 60 instead defines a convex curve relative to the first major surface 54 .
[0076] exist Figure 2A In the glass article 50, the support structure 64 is bonded to the second major surface 56 of the glass substrate 52 using adhesive beads 66. In an embodiment, the adhesive beads 66 are structural adhesives, such as polyurethane adhesives. Other materials are also possible, such as epoxy resins (e.g., 3M TM DP604NS, 3M TM DP125), silane-modified polymers (e.g., Teroson TMMS9399). In an embodiment, the material of adhesive bead 66 includes an elastic modulus of 0.1 MPa to 300 MPa. In addition, in an embodiment, when set and before curing, the material of adhesive bead 66 includes a viscosity of 1 kcps to 500 kcps. In an embodiment, adhesive bead 66 includes a thickness greater than or equal to 0.3 mm and less than or equal to 1.0 mm. In an embodiment, adhesive bead 66 includes a width greater than or equal to 1.5 mm and less than or equal to 2.0 mm (in a direction parallel to the first major surface 54 and the second major surface 56). The width of adhesive bead 66 may depend on the bezel width associated with support structure 64. For example, the width may correspond to the bezel width of support structure 64, which may extend inward from the periphery of support structure 64 and range from 1.0 mm to 15.0 mm.
[0077] In an embodiment, the support structure 64 facilitates mounting the glass article 50 to a vehicle interior mount (such as, for example, Figure 1 60 ). In addition, the support structure 64 has a support surface 65 that can be curved and holds the glass substrate 52 in its curved shape (at least in the curved region 60). In an embodiment, the glass substrate 52 is formed in such a way that the curved region 60 is not permanent. That is, if the glass substrate 52 is not bonded to the support structure 64 using the adhesive bead 66, the glass substrate 52 will rebound to a planar, non-curved configuration. Thus, the glass substrate 52 is stressed to create the curvature and remains stressed during the life of the glass article 50.
[0078] The stress in the glass substrate 52 tends to cause the glass substrate 52 to pull away from the support structure 64, which means that the adhesive bead 66 is also stressed. The stress caused by thermal cycling can further exacerbate this stress. In particular, the glass substrate 52 has a different thermal expansion coefficient than the thermal expansion coefficient of the support structure 64, which is typically a metal, composite or plastic component. The difference in thermal expansion coefficients means that the glass substrate 52 and the frame expand or contract by different amounts during thermal cycling between temperature extremes (e.g., as low as -40°C and as high as 80°C), thereby inducing additional stress in the adhesive bead 66. In order to avoid damage caused by thermal stress added to the normal mechanical stress associated with bending, the adhesive bead 66 has a shape described herein to suppress stress singularities at the interface between the adhesive bead 66, the support structure 64 and the glass substrate 52. Such stress singularity suppression can make the stress caused by bending and thermal cycling more predictable, thereby promoting more reliable part design. In addition, the adhesive bead shape described herein can reduce the peak stress in the tensile and sliding failure modes of the adhesive, making damage (e.g., delamination) less likely to occur during the service life of the glass article.
[0079] Figure 2B Another embodiment of a glass article 50 is depicted in a C-shaped glass configuration. Figure 2A Compared to the V-shaped configuration depicted in Figure 2B The C-shaped configuration has a larger curved region 60 and shorter flat sections 62a, 62b. V-shape and C-shape are just two examples of glass articles 50 that can be produced according to the present disclosure. In other embodiments, the glass article 50 can include a curved region 60 with opposite curvature to produce an S-shape, a curved region 60 followed by a flat section 62a to produce a J-shape, and a curved region 60 separated by a flat section 62a to produce a U-shape, etc.
[0080] The glass article 50 according to the present disclosure is formed by cold forming techniques. Generally speaking, the cold forming process involves forming a glass substrate 52 such as Figure 3 60 . As shown, a bending force is applied to the glass substrate 52 while positioned on the suction cup 68. As can be seen, the suction cup 68 has a curved forming surface 70, and the glass substrate 52 is bent to conform to the curved forming surface 70. Advantageously, it is easier to apply a surface treatment to the glass substrate 52 when the glass substrate 52 is flat before creating a curvature in the glass substrate 52, and cold forming allows the glass substrate 52 to be bent without damaging the surface treatment (compared to the tendency of high temperatures associated with hot forming techniques to damage the surface treatment, which requires a more complex process to apply the surface treatment to the curved article). In an embodiment, the cold forming process is performed at a temperature below the glass transition temperature of the glass substrate 52. In particular, the cold forming process can be performed at room temperature (e.g., about 20° C.) or a slightly higher temperature (e.g., 200° C. or less, 150° C. or less, 100° C. or less, or 50° C. or less).
[0081] In an embodiment, the bending force applied to the glass substrate 52 may be in the form of vacuum pressure through the suction cup 68. In an embodiment, the suction cup 68 includes an internal channel with a port on the forming surface 70 of the suction cup 68. When the glass substrate 52 is positioned on the forming surface 70, a vacuum is passed through the channel to hold the glass substrate 52 against the suction cup and conform to the curvature of the forming surface 70. In other embodiments, the forming surface 70 may use other techniques to hold the glass substrate 52 conform to the curvature. For example, the forming surface 70 may be a self-adhesive material that is configured to provide sufficient adhesion to hold the glass substrate 52 in a curved configuration during cold forming, or the suction cup 68 may operate in conjunction with a press or clamp that holds the glass substrate 52 conform to the forming surface 70 during cold forming.
[0082] exist Figure 3In the illustrated embodiment, the adhesive bead 66 is applied to the second major surface 56 of the glass substrate 52, and the support structure 64 is lowered onto the glass substrate 52. However, in other embodiments, the adhesive bead 66 may instead be applied to the support surface 65 of the support structure 64. In either case, the support structure 64 may compress the adhesive bead 66 between the support surface 65 and the second major surface 56 of the glass substrate 52, so that the adhesive bead 66 contacts both the support surface 65 and the second major surface 56. Figure 3 , adhesive bead 66 is applied to glass substrate 52 in a manner such that the shape traced by adhesive bead 66, i.e., a “bead path,” substantially matches the shape of support structure 64. In an embodiment, adhesive bead 66 defines a closed bead path, such that adhesive bead 66 is continuous on glass substrate 52. In other embodiments, adhesive bead 66 may have a discontinuous bead path, e.g., with breaks between segments of adhesive bead 66.
[0083] In an embodiment, the adhesive bead 66 is applied through a nozzle 71 having a circular port 73, such as Figure 3 Advantageously, such nozzles allow for ease of manufacturing because the orientation of the nozzle relative to the glass substrate 52 is not limited, as compared to certain nozzles having, for example, triangular ports, which are often aligned in a specific orientation relative to the glass sheet in order to apply a shaped adhesive bead in the proper location. Any suitable application technique may be used to apply the adhesive in an uncured shape. In addition, although Figure 3 The adhesive bead 66 is depicted as being applied to the glass substrate 52 while the glass substrate 52 is in a curved configuration over the suction cup 68, but the adhesive bead 66 may instead be applied to the glass substrate 52 while the glass substrate 52 is in a flat configuration such that the glass substrate 52 with the adhesive bead 66 applied thereto is subsequently curved over the molding surface 70 of the suction cup 68. Embodiments are also contemplated in which the adhesive bead 66 is first applied to the support structure 64 and then the adhesive bead 66 is brought into contact with the glass substrate 52.
[0084] In the depicted embodiment, once the adhesive beads 66 are cured, the glass substrate 52 is maintained in a curved configuration associated with the support structure 64. Thus, the glass substrate 52 is maintained out of mechanical equilibrium by the adhesive beads 66, and therefore, the glass substrate 52 applies bending stresses to the adhesive beads 66. In addition, the glass substrate 52 and the support structure 64 may be composed of materials with significantly different thermal expansion coefficients. When the glass article 50 is exposed to temperature changes, the different expansion and contraction of the glass substrate 52 and the support structure 64 may cause additional thermally induced stresses in the adhesive beads 66. In order to determine whether the glass article 50 is likely to exhibit the long life required for a particular application, such stresses should be modeled before constructing the glass article 50 to determine, for example, whether an appropriate adhesive is selected for a particular design. Although the previous discussion relates to an embodiment in which the glass substrate 52 is curved, the adhesive bead structures and related methods described herein are also applicable to embodiments in which the glass substrate 52 and the support structure 64 (or at least the support surface 65) are flat.
[0085] Figure 4 Depicts a cross-sectional view of a glass-adhesive interface 400. As shown, the glass-adhesive interface 400 is a cross-sectional view of a glass-adhesive interface 400 as described herein. Figure 2A , Figure 2B and Figure 3 The adhesive bead 66 is depicted where it contacts and bonds with the glass substrate 52 . Figure 4 Only a portion of glass-adhesive interface 400 near its edge (e.g., peripheral edge) is depicted. As shown, at edge 404 of glass-adhesive interface 400, adhesive bead 66 terminates thereat (e.g., edge 404 may coincide with an end of edge 406 of adhesive bead 66), adhesive bead 66 extends at an angle θ1 relative to contact area 402, where adhesive bead 66 contacts glass substrate 52. Edge 406 may correspond to an outer surface of adhesive bead 66. At edge 408 of glass substrate 52, glass substrate 52 extends at an angle θ2 relative to contact area 402. Although Figure 4 The glass substrate 52 and the adhesive bead 66 are depicted as having edges 406 and 408 that coincide with each other, but it should be understood that Figure 4 Only the overlap area between the adhesive bead 66 and the glass substrate 52 is depicted. Figure 2A , Figure 2B and Figure 3 In the depicted glass article 50, the edge of the adhesive bead 66 may be disposed at the peripheral edge of the glass substrate 52 (eg, the secondary surface 58, see Figure 2A ). Furthermore, although the contact area 402 is depicted as being flat, the contact area 402 may be curved in various embodiments, such as when the glass article 50 is curved and the glass substrate 52 is cold formed, as described herein.
[0086] For wedge geometries and / or dual material interfaces (e.g. Figure 4 402 ), elastic conjoint mechanics predicts infinite stresses at edge 404 and at the corners of each material (where edges 406 and 408 contact each other at the ends of contact region 402). In this configuration, the finite element model tends to exhibit stress singularities, where the calculated stress results at edges 406 and 408 diverge from each other depending on the mesh size used in the finite element model. For illustration, the finite element analysis is performed assuming a large gap between the elastic modulus of the glass substrate 52 (Young's modulus of approximately 40,000 MPa), the elastic modulus of the support structure (Young's modulus of approximately 70,000 MPa (aluminum) or 200,000 MPa (stainless steel)), and the elastic modulus of the adhesive bead (Young's modulus of approximately 5 MPa), so the glass substrate 52 and support structure 64 are treated as rigid bodies in the analysis. The interface between the adhesive bead 66, support structure 64, and glass substrate 52 is assumed to be perfectly bonded, which means that there is no relative displacement at the interface. The adhesive bead 66 is assumed to adopt linear and isotropic behavior (with a Poisson's ratio less than or equal to 0.5). The adhesive is assumed to have three degrees of freedom: (a) shear, in which a shear load is applied in a direction parallel to the glass substrate 52 and the support structure 64; (b) tension, in which the adhesive bead 66 is stretched in a direction perpendicular to the glass substrate 52 and the support structure 64; and (c) rotation, in which the glass substrate 52 is twisted relative to the support structure 64. In the analysis, a coordinate system is attached to the support structure 64.
[0087] In the finite element analysis according to this example, the cross section of the adhesive bead 66 (in the direction perpendicular to the first major surface 54 and the second major surface 56) is considered to be a unit square (1×1 mm 2 , in a plane extending perpendicular to the glass substrate 52 and the adhesive bead 66), assuming that the rigid top and bottom edges correspond to the glass substrate 52 and the support substrate 64, and that a unit force (tension and shear) or moment (rotation) is applied to the top edge of the adhesive bead 66 (corresponding to Figure 4 Several 2D models were generated, representing mesh sizes ranging from 1 mm to 10 -3 mm. Figure 5A 500 depicts the initial shape of the adhesive bead 66 in this simulation. In this simulation, it is assumed that the first angle θ1 (see Figure 4 ) is 90° (in the simulation, edge 406 extends at 90° relative to glass substrate 52). The simulation focuses on integration point 502, which represents the integration point closest to the corner point of adhesive bead 66 at edge 406 (see Figure 4 ). Figure 5B The results of the simulation are plotted in . As shown, finer mesh sizes result in much higher estimated stresses at the corners of the adhesive bead 66, varying by more than an order of magnitude over the range of mesh sizes considered. Such phenomena are described herein as "stress singularities," where the predicted stress values for various loading conditions vary with the mesh size used.
[0088] refer to Figure 4 In the modeling of the glass-adhesive interface 400, the material is modeled as elastic, isotropic and homogeneous. Fracture mechanics is used to evaluate crack propagation. Asymptotic solutions are used for different elastic planes of a perfect bond subjected to traction and are calculated near the vertex (edge 404) of the bond plane (corresponding to the contact area 402). These asymptotic solutions give the following relationship between the singular stress field at the free edge and the distance from the corner point:
[0089] σ~K a r λ-1 (1)
[0090] Where K a is the stress intensity factor, and λ-1 is the order of the stress singularity. Figure 4 The vector r in (denoted by ) is relatively small, and the subsequent terms of the additional stress component are approximately zero. According to Dundurs, J. Stress Intensity Factors in Two Bonded Elastic Layers Containing Crack Perpendicular on the Interface with Different Elastic Properties. Journal of Applied Mechanics, 1969, Vol. 36, pp. 650-652, the material properties at the interface can be described by two dimensionless material mismatch parameters, which are a combination of four elastic constants of the material at the interface:
[0091]
[0092] Among them G i and v i is the shear modulus and Poisson's ratio of material i at the interface. The parameter α is a measure of the relative stiffness of the contacting materials.
[0093] According to Suga, T., Elssner, G., et Schmauder, S. Composite parameters and mechanical compatibility of material joints. Journal of Composite Materials, 1988, Vol. 22, No. 10, pp. 917-934, the order of stress singularity λ-1 is defined and can be determined according to the characteristic equation:
[0094]
[0095] in
[0096]
[0097] As indicated by equations 2-5, the order λ-1 of the stress singularity depends on the material properties of the glass and adhesive, as well as the angles θ1 and θ2 at which the glass and adhesive extend relative to each other at the glass-adhesive. Analytical calculations were performed for various glass-adhesive interface designs based on the angle θ1 of the adhesive at the interface with the glass (while holding the material properties constant). In these examples, it was assumed that the edge 406 of the adhesive bead 66 was concave, so the angle θ1 was less than 90°. The results are plotted in Fig. 6AAs shown, within the range considered, the order of the stress singularity decreases as the adhesive angle at the interface decreases. In the case where θ1 is 45°, the order of the singularity is zero. As long as the modulus of the glass substrate 52 and the support structure 64 is an order of magnitude greater than the modulus of the adhesive bead 66, such a 45° angle will generally provide such a result. Such a result promotes improved part design by achieving appropriate stress estimation. Therefore, in an embodiment, the angle θ1 is greater than or equal to 35° and less than or equal to 70° (for example, greater than or equal to 35° and less than or equal to 60°, greater than or equal to 35° and less than or equal to 55°, greater than or equal to 35° and less than or equal to 50°, greater than or equal to 36° and less than or equal to 50°, greater than or equal to 37° and less than or equal to 50°, greater than or equal to 38° and less than or equal to 50°, greater than or equal to 39° and less than or equal to 50°, greater ... 2-5 herein, has a magnitude of less than or equal to 0.3 (less than or equal to 0.25, less than or equal to 0.20, less than or equal to 0.15, less than or equal to 0.1, less than or equal to 0.5).
[0098] Although Figure 4Only the glass-adhesive interface 400 is depicted in FIG. 4, but it should be understood that the values of θ1 provided herein are applicable not only to the angle at which the outer surface of the adhesive extends relative to the glass substrate at the interface between the glass and the adhesive (e.g., at the end of the adhesive bead 66), but also to the angle at which the outer surface of the adhesive extends relative to the support structure at the interface between the glass and the support structure. That is, the values of θ1 described herein correspond to the angle at which the adhesive extends relative to another material having different elastic properties (in terms of Young's modulus) at the corners of the adhesive bead ("corner" means the intersection between the outer surface of the adhesive bead and the end face of the adhesive bead that is combined with other materials). In some embodiments, the angles at the corners of the adhesive bead 66 may match each other so that the adhesive bead 66 includes a symmetrical shape. In other embodiments, the corner angle of the adhesive bead at the first interface (glass-adhesive interface) may not match the corner angle of the adhesive bead at the second interface (the interface between the adhesive bead 66 and the support structure 64), but both corner angles are within any one of the ranges provided herein for θ1.
[0099] Two-dimensional finite element analysis for various loading modes was also performed to determine the order of singularities as a function of angle Θ1 for the shear loading case. Figure 6B The results of the two failure modes are depicted in FIG. Mode I represents interface separation, while Mode II represents interface sliding. As shown, an angle θ1 in the range of 40° to 50° results in the lowest magnitude of stress singularity in this case, and an angle of about 42° provides no stress singularity for the interface sliding mode, and an angle of about 48° provides no stress singularity for the interface separation mode. In an embodiment, the angle θ1 may be in the range of 42° to 48° to minimize singularities for both failure modes under shear loading.
[0100] To determine the adhesive angle at the interface ( Figure 47A depicts the relationship between θ1 (depicted in FIG. 7A ) and stress singularity, using finite element model simulation to simulate different sections of adhesive. The values of θ1 90° (corresponding to the case where the edge 406 of the adhesive bead extends perpendicular to the glass substrate 52 before the load is applied), 67°, 57°, 46° and 37° (each of the aforementioned angles is lower than 90°, indicating that the edge 406 includes a concave shape with different radii of curvature, so that the adhesive bead 66 extends at the same relative angle relative to the glass substrate 52 and the support structure 64 at the end of the edge 406). FIG. 7A depicts the results when a unit shear load is applied to the adhesive bead 66 (FIG. 7A depicts the maximum normal stress in the top column and the shear stress in the bottom column). FIG. 7B depicts the results when a unit tensile load is applied to the adhesive bead 66 (FIG. 7B depicts the maximum normal stress in the top column and the shear stress in the bottom column). As shown in the figure, for both load conditions, a reduction in θ1 generally reduces the magnitude of the maximum stress predicted by the finite element model. 7A , for example, when angle θ1 is less than 57°, the areas of the adhesive bead that are subject to relatively high stress are removed from the corners of adhesive bead 66. That is, for example, when subjected to shear loading, the areas of greatest stress are not at the corners of the adhesive bead and are also removed from contact area 402 (see FIG. Figure 4 ). The maximum stress typically occurs in the body or bulk of the adhesive bead 66. Existing finite element models are typically able to predict stresses within the bulk of the material (rather than at the bi-material interface). Therefore, the adhesive bead structure described herein not only reduces the maximum stress (especially when the angle θ1 is greater than or equal to 40° and less than or equal to 50°), but the structure also advantageously locates the peak stress in the body of the adhesive bead 66, thereby making the stress behavior more predictable, thereby leading to a more reliable part design.
[0101] As shown in Figures 7A and 7B, the concave example with angle θ1 = 46° exhibits the lowest magnitude of stress (in terms of normal stress and shear stress) for both tensile and shear load conditions. It is noteworthy that, although the shear load condition of this example exhibits relatively high shear stress values at the corners of the adhesive bead 66, the order of the stress singularity is still reduced, as indicated by the relatively larger area of the relatively high stress region. Such larger large stress regions will make the calculation results less dependent on the mesh size, and the behavior of the resulting product more predictable. The lower magnitude of stress will also tend to make the resulting product more reliable than when the angle θ1 is 90° or greater (such as in a straight edge or convex adhesive bead structure).
[0102] Experiments were conducted with a straight edge design of adhesive bead 66 (where angle θ1 was 90°), and failure often occurred at contact area 402 (see FIG. 4 ) due to defects on the glass surface or local variations in the chemical composition (e.g., of the adhesive bead). Figure 4 ) at the interface or in the bulk of the adhesive, the crack propagation behavior should be considered in order to evaluate the part behavior of the glass article. The crack can change the overall response of the glass article to a specific load. The lower stress at the contact area 402 provided by the concave adhesive beads described herein makes such crack formation less likely. The concave bead design described herein can make cohesive failure (in the bulk of the adhesive) more likely to occur, which makes high strength variability due to interface changes less likely.
[0103] A 3D finite element analysis was also performed. For the 3D case, the effect of the concave bead shape is similar to the 2D case described herein with respect to FIGS. 7A and 7B . For the straight edge case, the adhesive bead 66 was modeled as a unit cube (1×1×1 mm 3 ). For the concave case, the adhesive bead 66 is modeled as having four concave outer surfaces with a radius of curvature such that the angle θ1 of each outer surface is 45°.
[0104] FIG. 8A to FIG. 8D 3D results depicting shear load conditions. Figure 8B As shown, the adhesive bead 800 modeled in this example includes a concave shape, a top surface 802, a bottom surface 804, and a plurality of outer surfaces 806. In the simulation, the top surface 802 is bonded to a glass substrate (corresponding to the embodiment of the present invention). Figures 2A to 4 The glass substrate 52 described herein) is provided with the bottom surface 804 and the support structure (corresponding to Figures 2A to 4 64) described herein. In this example, each of the plurality of outer surfaces 806 is modeled as having the same concave shape extending the entire distance between the glass substrate and the support structure. Such an example represents a case where the incorporated glass article includes a plurality of discrete and separate adhesive beads connecting the glass substrate and the support structure. Such a set of discrete adhesive beads can be arranged along the lines described herein with respect to Figure 3 The described bead path is dispensed and extends along a peripheral portion of the glass substrate. Embodiments are also contemplated where the adhesive bead is a continuous strip of material dispensed along the bead path, in which case the adhesive bead would include only two outer surfaces.
[0105] exist FIG. 8A to FIG. 8D In the figure, the upper right corner of the depicted bead represents the outer edge of the glass-adhesive interface (corresponding to Figure 4 edge 404 depicted in FIG. Fig. 8A Simulation results depicting the open failure mode (interfacial separation between two materials in a direction perpendicular to the interface) at the interface of a straight edge design. Figure 8B Simulation results depicting the open failure mode at the interface of a concave design. Figure 8CSimulation results depicting the sliding failure mode (interfacial separation between two materials in a direction parallel to the interface) at the interface of a straight edge design. Fig.8D Simulation results depicting the sliding failure mode at the interface of the concave design. FIG. 8A to FIG. 8B As shown, for the concave case, the maximum mode 1 (open) stress is reduced by 68%. Figure 8C and Fig.8D As shown, for the concave shape, the maximum Mode II (sliding) stress is reduced by 15%.
[0106] 9A to 9D Plot the results for the tensile load case. Fig.9A Plotting the tensile loading results for the open failure mode associated with the straight edge case. Fig. 9B Tensile loading results depicting the open failure mode for the concave edge case. Fig. 9C Plotting the tensile loading results for the sliding failure mode associated with the straight edge case. Fig.9D Tensile loading results for the sliding failure mode depicting the concave edge case. Fig.9A and Fig. 9B As shown in Figure 2, the maximum stress in the open failure mode (mode I) is reduced by 58% due to the concave edge structure. Fig. 9C and Fig.9D As shown in Figure 2, the maximum stress in the sliding failure mode (mode II) is reduced by 58% due to the concave edge structure. 8A to 9D For each of the loading and failure mode results depicted in , the location of maximum stress is removed from the corner point in the concave bead and instead is in the bulk of the adhesive.
[0107] A further 2D finite element analysis was performed to determine the effect of the adhesive bead design described herein on stresses induced by coefficient of expansion (“CTE”) mismatch. The test was numerically applied in two dimensions by fixing the top surface of a glass substrate disposed above the adhesive bead. The bottom surface of the adhesive bead was also fixed to an aluminum frame. The assembly was heated from an initial temperature of 22°C to a final temperature of 90°C. Due to the relatively large CTE mismatch between the adhesive, glass, and aluminum (where the CTE of each component is 1.5E-4 / °K, 7.9E-6 / °K, and 2.1E-5 / °K, respectively), the adhesive will be in compression at the end of heating. The simulation results are depicted in FIG. 10A to FIG. 10D middle. Fig. 10A Depicting the results of an open failure mode for the straight edge case. Fig. 10B Results for the open failure mode for the concave edge case (where Θ1 = 45°) are depicted. Fig. 10C Depicting the results of the sliding failure mode for the straight edge case. Fig. 10D Results showing the sliding failure mode for the concave edge case. Fig. 10A and Fig. 10CAs shown in , the straight edge design exhibits singularities at the corners. Fig. 10B and Fig. 10D As shown, the concave shape exhibits a significant reduction in maximum stress (86% reduction in open failure mode stress and 64% reduction in sliding failure mode stress). The concave case also reduces singularities, with the size of the maximum stress region at the corner being larger than in the straight edge case. These results indicate that the concave adhesive bead design described herein improves the stress performance of a variety of glass articles when subjected to stresses from many different sources.
[0108] Although the adhesive beads described with respect to the previous examples have been described as having a "concave" shape, it should be understood that adhesive beads having a wide variety of shapes are contemplated and within the scope of the present disclosure. In some embodiments, the outer surface of the adhesive bead (extending between the glass substrate and the support structure) is continuously curved throughout its entirety (e.g., the outer surface of the adhesive bead may be concave and curved with a single radius of curvature, or include a variable radius of curvature over the entire distance between the glass substrate and the support structure). In other embodiments, the outer surface of the adhesive bead may not be curved over the entire distance between the glass substrate and the support structure. That is, in an embodiment, a portion of the outer surface of the adhesive bead may be planar or even convex. Although a concave shape with a continuous curvature may be preferred for ease of manufacturing and localizing the maximum stress in the bulk of the adhesive bead, it has been found that the magnitude of the limited stress singularity described herein is particularly advantageous. Therefore, any adhesive bead structure that limits the angle θ1 extending from the adhesive at the adhesive interface relative to the glass substrate and the support structure to within the range described herein may be used. Therefore, the adhesive shaping techniques described herein (e.g., the adhesive shaping techniques described herein) are not necessarily limited to the adhesive bead. Fig.11A and Fig. 11B The described shaped member or shaped surface of the sacrificial material) can be customized to provide any suitable shape for the adhesive bead.
[0109] Fig.11A A portion of a glass article 1100 is schematically depicted while an adhesive bead 1110 of the glass article 1100 is curing according to an exemplary embodiment of the present disclosure. For example, the glass article 1100 may correspond to the glass article 1100 described herein. FIG. 2A to FIG. 10B Described glass article 50. Glass article 1100 is depicted as including a glass substrate 1102 having a major surface 1104, a support structure 1106 having a support surface 1108, and adhesive beads 1110. Fig.11AThe glass article 1100 is depicted at a point in time when the adhesive bead 1110 is in contact with both the glass substrate 1102 and the support structure 1106 and before the adhesive is fully cured. When in such a state, the pre-cured adhesive comprising the adhesive bead 1110 is in a ductile state and is therefore capable of being shaped to have a portion located at the interface with the glass substrate 1102 and the support structure 1106. Figure 4 The angle θ1 depicted in describes the angle within the range.
[0110] like Fig.11A As shown, when the adhesive bead 1110 is in an uncured or partially cured state, the adhesive bead 1110 is in contact with the plurality of shaping members 1112 and 1114. In an embodiment, the plurality of shaping members 1112 and 1114 can be moved relative to the glass substrate 1102 and the support structure 1106 (e.g., by hand, by attachment to a mechanical assembly including a suitable actuator), so that they can be configured to form an adhesive shaping cavity 1115 with a desired positioning on the glass substrate 1102. The outer boundary of the adhesive shaping cavity 1115 can be delimited by the shaping surfaces 1116 and 1118 of the plurality of shaping members 1112 and 1114. In an embodiment, before depositing the adhesive, the plurality of shaping members 1112 and 1114 are disposed in contact with the glass substrate 1102 or the support structure 1106. Therefore, in an embodiment, the adhesive is disposed in the adhesive shaping cavity 1115 at least partially defined by the plurality of shaping members 1112 and 1114.
[0111] In an embodiment, after dispensing adhesive on one of the glass substrate 1102 and the support structure 1106, the plurality of shaping members 1112 and 1114 are brought into contact with the adhesive bead 1110. In one example, the adhesive bead 1110 may be disposed on the glass substrate 1102 while the glass substrate 1102 is cold-formed by applying a suitable force thereto (e.g., by a vacuum chuck or a clamp). After deposition, but before the adhesive bead 1110 is fully cured, the plurality of shaping members 1112 and 1114 may be brought into contact with the glass substrate 1102 and the adhesive bead 1110 so as to deform the adhesive bead 1110 so that its outer surface assumes the shape of the shaping surfaces 1116 and 1118. In an embodiment, before the adhesive is fully bent (e.g., before the plurality of shaping members 1112 and 1114 are brought into contact with the adhesive bead 1110), the support structure 1106 is spaced a distance 1120 from the glass substrate 1102. The distance 1120 may correspond to the desired height of the adhesive bead 1110 after curing (e.g., measured in a direction perpendicular to the major surface 1104 of the glass substrate 1102). In an embodiment, after contacting the plurality of shaping members 1112 and 1114 with the adhesive bead 1110, the support structure 1106 may be positioned a distance 1120 from the glass substrate 1102.
[0112] The number of shaping members in the plurality of shaping members 1112 and 1114 may vary depending on the desired peripheral shape of the adhesive bead 1110. In the depicted embodiment, for example, the plurality of shaping members 1112 and 1114 include an inner shaping member 1112 and an outer shaping member 1114. The inner shaping member 1112 may be disposed near an inner edge 1122 of the support structure 1106. The outer shaping member 1114 may be disposed near an outer edge 1124 of the support structure 1106. In an embodiment, the shapes of the inner shaping member 1112 and the outer shaping member 1114 correspond to the support structure 1106. For example, in an embodiment, the support structure 1106 is a frame attached to a peripheral portion of the major surface 1104 of the glass substrate 1102, and the inner shaping member 1112 and the outer shaping member 1114 are also frame-shaped. The inner shaping member 1112 and the outer shaping member 1114 can be formed of multiple sections that can move independently of each other to facilitate forming such shapes. The specific shape of the adhesive shaping cavity 1115 can vary according to the implementation, and the shapes and configurations of the multiple shaping members 1112 and 1114 can vary.
[0113] In an embodiment, when forming the adhesive shaping cavity 1115, more than two shaping members may contact the adhesive bead 1110. In an embodiment, the number of shaping members contacting the adhesive bead 1110 corresponds to the number of outer surfaces of the adhesive bead 1110. For example, in order to form the adhesive shaping cavity 1115 described herein, Figure 8B and Fig.8D In the adhesive bead structure described above, four shaping members may contact the adhesive bead 1110. In an embodiment, a plurality of shaping members are contacted with a plurality of individual adhesive beads disposed on one of the glass substrate 1102 and the support structure 1106 to form a plurality of individual adhesive shaping cavities. Any suitable number of shaping members may be used depending on the pattern of the adhesive distributed between the support structure 1106 and the glass substrate 1102.
[0114] Each of the plurality of shaping members 1112 and 1114 may have any suitable structure, depending on the desired shape of the adhesive shaping cavity 1115 and the shape of the support structure 1106. In the depicted embodiment, for example, the outer shaping member 1114 includes an arm 1126 and a shaping extension 1128 extending at an angle relative to the arm 1126. The shaping extension 1128 may have a maximum dimension 1130 corresponding to a distance 1120 at which the glass substrate 1102 is disposed relative to the support structure 1106 when the adhesive is cured. The shaping extension 1128 includes a shaping surface 1118 and is generally configured to be inserted between the glass substrate 1102 and the support structure 1106 to form the adhesive shaping cavity 1115. The arm 1126 extending at an angle relative to the shaping extension 1128 advantageously helps to manipulate the positioning of the outer shaping member 1114 relative to the glass substrate 1102. The inner shaping member 1112 may have a similar structure to the outer shaping member 1114.
[0115] In an embodiment, the plurality of shaping members 1112 and 1114 (or at least the portion thereof contacting the glass substrate 1102, the support structure 1106, and the adhesive bead 1110) are formed of a material selected not to adhere to the glass substrate 1102, the support structure 1106, and the adhesive bead 1110 during the curing of the adhesive. For example, the plurality of shaping members 1112 and 1114 may not be bonded to the adhesive bead 1110. In an embodiment, the plurality of shaping members 1112 and 1114 are formed of a suitable metal material that does not bond to the adhesive. A suitable non-stick coating (e.g., a polytetrafluoroethylene gasket or anodized aluminum) may be applied to the plurality of shaping members 1112 and 1114 to reduce the possibility of bonding. Such a structure advantageously facilitates the adhesive bead 1110 to be shaped to conform to the shaping surfaces 1116 and 1118, and facilitates the removal of the plurality of shaping members 1112 and 1114 without changing the shape of the adhesive bead 1110 or damaging the glass substrate 1002 or the support structure 1006.
[0116] Fig. 11B A glass article 1100 is depicted that is formed using a set of alternative shaping components. Fig. 11B As shown, multiple sacrificial shaping components 1140 and 1142 are used to form the Fig. 11BThe shaping surfaces 1116 and 1118 described. A plurality of sacrificial shaping members 1140 and 1142 may be formed and / or disposed on the glass substrate 1102 before the adhesive bead 1110 is deposited on the glass substrate 1102. The plurality of sacrificial shaping members 1140 and 1142 may be a suitable material that can be removed from the glass substrate 1102 without damaging the adhesive bead 1110, the glass substrate 1102, and the support structure 1106 after the adhesive of the adhesive bead 1110 is fully cured. In an embodiment, the sacrificial shaping members 1140 and 1142 are formed of a suitable wax that can maintain a shape during the curing of the adhesive and then melt due to heating to a temperature less than or equal to 70° C. (e.g., greater than or equal to 46° C. and less than or equal to 68° C.) to avoid changing the structure of the adhesive bead 1110. Depending on the desired structure of the adhesive bead, such a wax structure may be formed on the glass substrate 1102 by a suitable process (e.g., molding, additive manufacturing) before depositing the adhesive in any suitable configuration. Prior to the curing of the adhesive beads, the support structure 1106 may be contacted with a plurality of sacrificial shaping members 1140 and 1142 to complete the adhesive shaping cavity 1115. Any sacrificial material that can be removed after the adhesive is cured by a process that does not damage the adhesive beads 1110 may be used. In an embodiment, for example, the plurality of sacrificial shaping members 1140 and 1142 may be magnetically held in place during the curing of the adhesive and subsequently removed by cutting or removing the magnets. Any suitable temporary shaping member structure may be used. In an embodiment, the plurality of sacrificial shaping members 1140 and 1142 may be formed on the support structure 1106, and then the glass substrate 1102 may be contacted with the support structure 1106.
[0117] In an embodiment, adhesive may be dispensed into the adhesive shaping cavity by at least one of the plurality of shaping members. For example, one of the plurality of shaping members may include a channel extending therethrough, and adhesive may be dispensed after the adhesive shaping cavity 1115 includes a closed cavity (except for the end of the channel).
[0118] Fig.12 A flow chart depicting a method 1200 of attaching a glass substrate to a support structure using an adhesive bead structure according to an exemplary embodiment of the present disclosure. The method 1200 may be used, for example, to form a method described herein with respect to Figure 2A and Figure 2B The glass article 50 described herein or in any other configuration. Figures 2A to 4Various components are described to help describe the method. At block 1202, a glass substrate 52 is provided and shaped. The glass substrate 52 may be commercially available or formed using any suitable glass forming technique (e.g., a pull-down technique, a float forming technique). In embodiments, the glass substrate 52 is cold formed and the shaping may include bending the glass substrate 52 to have a desired curvature. Such bending may include applying a bending force to the glass substrate 52 to bend the glass substrate 52 to conform to a support surface. In embodiments, such bending is performed by Figure 3 The suction cup 68 depicted in FIG. 6 occurs, but any suitable cold forming technique may be used.
[0119] At block 1204, adhesive is dispensed onto the glass substrate 52. Any suitable adhesive may be used (e.g., structural adhesive, optically clear adhesive, pressure sensitive adhesive, UV curable adhesive). The adhesive may include a suitable viscosity to facilitate dispensing by a suitable method. The adhesive may be dispensed, for example, by Figure 3 The coating gun or nozzle 71 depicted in FIG. dispenses along a bead path. In an embodiment, the adhesive is dispensed in a continuous strip. In an embodiment, the adhesive is dispensed in a plurality of discrete beads. In an embodiment, the adhesive is not initially dispensed on the glass substrate 52, but rather on the support structure 64.
[0120] At block 1206, a plurality of shaping members are contacted with the adhesive before the adhesive is fully cured to form an adhesive shaping cavity with the support structure. Fig.11A The plurality of shaping members 1112 and 1114 described herein are provided and brought into contact with the adhesive by moving them through a suitable mechanism (e.g., by hand or a suitable actuator assembly). Fig. 11B A plurality of sacrificial shaping members 1240 and 1242 are depicted and are in contact with the adhesive when the adhesive is dispensed due to their presence on the glass substrate 52 (or support structure 64). The support structure 64 can move relative to the glass substrate 52 to contact the shaping members, thereby enclosing the adhesive shaping cavity.
[0121] At box 1208, contact between the adhesive and the multiple shaping members is maintained during the shaping period. In an embodiment (such as when multiple sacrificial shaping members 1140 and 1142 are used), contact is maintained until the adhesive is fully cured to prevent the removal of the shaping members from changing the shape of the adhesive. In an embodiment, contact is maintained at least until the adhesive is able to maintain the shape of the shaping surface of the shaping member without contact. Such a shortest period of time can be determined based on the curing conditions and curing rate of the adhesive. Contact is maintained during the curing of the adhesive under curing conditions determined by the adhesive used (for example, under exposure to radiation, at a specific temperature). At 1210, the adhesive is fully cured to form an adhesive bead 66, so that the angles at the corners of the adhesive bead 66 at the glass-adhesive interface and at the interface between the support structure and the adhesive have angles that are within the range described herein for Figure 4 The angle θ1 depicted in provides a value within any of the ranges provided.
[0122] Glass material
[0123] refer to Fig.13 In an embodiment, the glass substrate 52 has a thickness t, which is substantially constant over the width and length of the glass substrate 52 and is defined as the distance between the first major surface 54 and the second major surface 56. In various embodiments, T may refer to an average thickness or a maximum thickness of the glass substrate 52. In addition, the glass substrate 52 includes a width W, which is defined as a first maximum dimension of one of the first major surface 54 or the second major surface 56 that is orthogonal to the thickness t, and a length L, which is defined as a second maximum dimension of one of the first major surface 54 or the second major surface 56 that is orthogonal to both the thickness and the width. In other embodiments, W and L may be the average width and average length of the glass substrate 52, respectively, and in other embodiments, W and L may be the maximum width and maximum length of the glass substrate 52, respectively (e.g., for a glass substrate having a variable width or length).
[0124] In various embodiments, the thickness t is 2 mm or less. Specifically, the thickness t is 0.30 mm to 2.0 mm. For example, the thickness t may be about 0.30 mm to about 2.0 mm, about 0.40 mm to about 2.0 mm, about 0.50 mm to about 2.0 mm, about 0.60 mm to about 2.0 mm, about 0.70 mm to about 2.0 mm, about 0.80 mm to about 2.0 mm, about 0.90 mm to about 2.0 mm, about 1.0 mm to about 2.0 mm, about 1.1 mm to about 2.0 mm, about 1.2 mm to about 2.0 mm, about 1.3 mm to about 2.0 mm, about 1.4 mm to about 2.0 mm, about 1.5 mm to about 2.0 mm, about 0.30 mm to about 1.9 ...0 mm, about 1.1 mm to about 2.0 mm, about 1.2 mm to about In some embodiments, t is within the range of about 0.30 mm to about 0.8 mm, about 0.30 mm to about 1.7 mm, about 0.30 mm to about 1.6 mm, about 0.30 mm to about 1.5 mm, about 0.30 mm to about 1.4 mm, about 0.30 mm to about 1.4 mm, about 0.30 mm to about 1.3 mm, about 0.30 mm to about 1.2 mm, about 0.30 mm to about 1.1 mm, about 0.30 mm to about 1.0 mm, about 0.30 mm to about 0.90 mm, about 0.30 mm to about 0.80 mm, about 0.30 mm to about 0.70 mm, about 0.30 mm to about 0.60 mm, or about 0.30 mm to about 0.40 mm. In other embodiments, t falls within any one of the exact numerical ranges set forth in this paragraph.
[0125] In various embodiments, the width W is between 5 cm and 250 cm, about 10 cm to about 250 cm, about 15 cm to about 250 cm, about 20 cm to about 250 cm, about 25 cm to about 250 cm, about 30 cm to about 250 cm, about 35 cm to about 250 cm, about 40 cm to about 250 cm, about 45 cm to about 250 cm, about 50 cm to about 250 cm, about 55 cm to about 250 cm, about 60 cm to about 250 cm, about 65 cm to about 250 cm, about 70 cm to about 250 cm, about 75 cm to about 250 cm, about 80 cm to about 250 cm, about 85 cm to about 250 cm, about 90 cm to about 250 cm, about 95 cm to about 250 cm, about 100 cm to about 250 cm, about 110 cm to about 250 cm, In some embodiments, W is from about 120cm to about 250cm, from about 130cm to about 250cm, from about 140cm to about 250cm, from about 150cm to about 250cm, from about 5cm to about 240cm, from about 5cm to about 230cm, from about 5cm to about 220cm, from about 5cm to about 210cm, from about 5cm to about 200cm, from about 5cm to about 190cm, from about 5cm to about 180cm, from about 5cm to about 170cm, from about 5cm to about 160cm, from about 5cm to about 150cm, from about 5cm to about 140cm, from about 5cm to about 130cm, from about 5cm to about 120cm, from about 5cm to about 110cm, from about 5cm to about 110cm, from about 5cm to about 100cm, from about 5cm to about 90cm, from about 5cm to about 80cm, or from about 5cm to about 75cm. In other embodiments, W falls within any one of the exact numerical ranges set forth in this paragraph.
[0126] In various embodiments, the length L is between about 5 cm and about 2500 cm, about 5 cm and about 2000 cm, about 4 cm and about 1500 cm, about 50 cm and about 1500 cm, about 100 cm and about 1500 cm, about 150 cm and about 1500 cm, about 200 cm and about 1500 cm, about 250 cm and about 1500 cm, about 300 cm and about 1500 cm, about 350 cm and about 1500 cm, about 400 cm and about 1500 cm, about 450 cm and about 1500 cm, about 500 cm and about 1500 cm, about 550 cm and about 1500 cm, about 600 cm and about 1500 cm, about 650 cm and about 1500 cm, about 650 cm and about 1500 cm. In some embodiments, L is in the range of about 1500cm to about 1500cm, about 700cm to about 1500cm, about 750cm to about 1500cm, about 800cm to about 1500cm, about 850cm to about 1500cm, about 900cm to about 1500cm, about 950cm to about 1500cm, about 1000cm to about 1500cm, about 1050cm to about 1500cm, about 1100cm to about 1500cm, about 1150cm to about 1500cm, about 1200cm to about 1500cm, about 1250cm to about 1500cm, about 1300cm to about 1500cm, about 1350cm to about 1500cm, about 1400cm to about 1500cm, or about 1450cm to about 1500cm. In other embodiments, L falls within any one of the exact numerical ranges set forth in this paragraph.
[0127] In embodiments, the glass substrate 52 may be formed of any suitable glass composition including soda-lime glass, aluminosilicate glass, borosilicate glass, boroaluminosilicate glass, alkali-containing aluminosilicate glass, alkali-containing borosilicate glass, and alkali-containing boroaluminosilicate glass.
[0128] Unless otherwise specified, the glass compositions disclosed herein are described in units of mole percent (mol %) analyzed on an oxide basis.
[0129] In one or more embodiments, the glass composition may include SiO in an amount within a range from about 66 mol% to about 80 mol%, about 67 mol% to about 80 mol%, about 68 mol% to about 80 mol%, about 69 mol% to about 80 mol%, about 70 mol% to about 80 mol%, about 72 mol% to about 80 mol%, about 65 mol% to about 78 mol%, about 65 mol% to about 76 mol%, about 65 mol% to about 75 mol%, about 65 mol% to about 74 mol%, about 65 mol% to about 72 mol%, or about 65 mol% to about 70 mol%, and all ranges and sub-ranges therebetween.
[0130] In one or more embodiments, the glass composition includes Al2O3 in an amount greater than about 4 mol% or greater than about 5 mol%. In one or more embodiments, the glass composition includes Al2O3 in a range of greater than about 7 mol% to about 15 mol%, greater than about 7 mol% to about 14 mol%, about 7 mol% to about 13 mol%, about 4 mol% to about 12 mol%, about 7 mol% to about 11 mol%, about 8 mol% to about 15 mol%, about 9 mol% to about 15 mol%, about 9 mol% to about 15 mol%, about 10 mol% to about 15 mol%, about 11 mol% to about 15 mol%, or about 12 mol% to about 15 mol%, and all ranges and sub-ranges therebetween. In one or more embodiments, the upper limit of Al2O3 may be about 14 mol%, 14.2 mol%, 14.4 mol%, 14.6 mol%, or 14.8 mol%.
[0131] In one or more embodiments, the glass layer(s) herein are described as aluminosilicate glass articles or include aluminosilicate glass compositions. In such embodiments, the glass composition or article formed from the glass composition includes SiO2 and Al2O3 and is not a soda-lime silicate glass. In this regard, the glass composition or article formed from the glass composition includes Al2O3 in an amount of about 2 mol% or greater, 2.25 mol% or greater, 2.5 mol% or greater, about 2.75 mol% or greater, about 3 mol% or greater.
[0132] In one or more embodiments, the glass composition includes B2O3 (e.g., about 0.01 mol% or greater). In one or more embodiments, the glass composition includes B2O3 in an amount ranging from about 0 mol% to about 5 mol%, from about 0 mol% to about 4 mol%, from about 0 mol% to about 3 mol%, from about 0 mol% to about 2 mol%, from about 0 mol% to about 1 mol%, from about 0 mol% to about 0.5 mol%, from about 0.1 mol% to about 5 mol%, from about 0.1 mol% to about 4 mol%, from about 0.1 mol% to about 3 mol%, from about 0.1 mol% to about 2 mol%, from about 0.1 mol% to about 1 mol%, from about 0.1 mol% to about 0.5 mol%, and all ranges and sub-ranges therebetween. In one or more embodiments, the glass composition is substantially free of B2O3.
[0133] As used herein, the phrase "substantially free" with respect to a component of a composition means that the component is not actively or intentionally added to the composition during initial compounding, but may be present as an impurity in an amount of less than about 0.001 mole %.
[0134] In one or more embodiments, the glass composition optionally includes P2O5 (e.g., about 0.01 mol% or greater). In one or more embodiments, the glass composition includes a non-zero amount of P2O5, up to and including 2 mol%, 1.5 mol%, 1 mol%, or 0.5 mol%. In one or more embodiments, the glass composition is substantially free of P2O5.
[0135] In one or more embodiments, the glass composition may include a total amount (total amount of alkali metal oxides such as Li2O, Na2O, K2O, Rb2O, and Cs2O) of greater than or equal to about 8 mol%, greater than or equal to about 10 mol%, or greater than or equal to about 12 mol% of R2O. In some embodiments, the glass composition includes a total amount of R2O in a range from about 8 mol% to about 20 mol%, from about 8 mol% to about 18 mol%, from about 8 mol% to about 16 mol%, from about 8 mol% to about 14 mol%, from about 8 mol% to about 12 mol%, from about 9 mol% to about 20 mol%, from about 10 mol% to about 20 mol%, from about 11 mol% to about 20 mol%, from about 12 mol% to about 20 mol%, from about 13 mol% to about 20 mol%, from about 10 mol% to about 14 mol%, or from 11 mol% to about 13 mol%, and all ranges and sub-ranges therebetween. In one or more embodiments, the glass composition may be substantially free of Rb2O, Cs2O, or both Rb2O and Cs2O. In one or more embodiments, R2O may include only the total amount of Li2O, Na2O, and KO. In one or more embodiments, the glass composition may include at least one alkali metal oxide selected from Li2O, Na2O, and KO, wherein the alkali metal oxide is present in an amount greater than about 8 mol% or more.
[0136] In one or more embodiments, the glass composition includes NaO in an amount greater than or equal to about 8 mol%, greater than or equal to about 10 mol%, or greater than or equal to about 12 mol%. In one or more embodiments, the composition includes NaO in a range from about 8 mol% to about 20 mol%, about 8 mol% to about 18 mol%, about 8 mol% to about 16 mol%, about 8 mol% to about 14 mol%, about 8 mol% to about 12 mol%, about 9 mol% to about 20 mol%, about 10 mol% to about 20 mol%, about 11 mol% to about 20 mol%, about 12 mol% to about 20 mol%, about 13 mol% to about 20 mol%, about 10 mol% to about 14 mol%, or 11 mol% to about 16 mol%, and all ranges and sub-ranges therebetween.
[0137] In one or more embodiments, the glass composition includes less than about 4 mol % K2O, less than about 3 mol % K2O, or less than about 1 mol % K2O. In some cases, the glass composition may include KO in an amount in a range from about 0 mol% to about 4 mol%, about 0 mol% to about 3.5 mol%, about 0 mol% to about 3 mol%, about 0 mol% to about 2.5 mol%, about 0 mol% to about 2 mol%, about 0 mol% to about 1.5 mol%, about 0 mol% to about 1 mol%, about 0 mol% to about 0.5 mol%, about 0 mol% to about 0.2 mol%, about 0 mol% to about 0.1 mol%, about 0.5 mol% to about 4 mol%, about 0.5 mol% to about 3.5 mol%, about 0.5 mol% to about 3 mol%, about 0.5 mol% to about 2.5 mol%, about 0.5 mol% to about 2 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.5 mol% to about 1 mol%, and all ranges and sub-ranges therebetween. In one or more embodiments, the glass composition may be substantially free of KO.
[0138] In one or more embodiments, the glass composition is substantially free of Li2O.
[0139] In one or more embodiments, the amount of Na2O in the composition may be greater than the amount of Li2O. In some cases, the amount of Na2O may be greater than the combined amount of Li2O and K2O. In one or more alternative embodiments, the amount of Li2O in the composition may be greater than the amount of Na2O or the combined amount of Na2O and K2O.
[0140] In one or more embodiments, the glass composition may include a total amount of RO (total amount of alkaline earth oxides such as CaO, MgO, BaO, ZnO, and SrO) in the range of about 0 mol% to about 2 mol%. In some embodiments, the glass composition includes a non-zero amount of RO, up to about 2 mol%. In one or more embodiments, the glass composition includes RO in an amount of about 0 mol% to about 1.8 mol%, about 0 mol% to about 1.6 mol%, about 0 mol% to about 1.5 mol%, about 0 mol% to about 1.4 mol%, about 0 mol% to about 1.2 mol%, about 0 mol% to about 1 mol%, about 0 mol% to about 0.8 mol%, about 0 mol% to about 0.5 mol%, and all ranges and sub-ranges therebetween.
[0141] In one or more embodiments, the glass composition includes CaO in an amount less than about 1 mol%, less than about 0.8 mol%, or less than about 0.5 mol%. In one or more embodiments, the glass composition is substantially free of CaO. In some embodiments, the glass composition includes MgO in an amount of about 0 mol% to about 7 mol%, about 0 mol% to about 6 mol%, about 0 mol% to about 5 mol%, about 0 mol% to about 4 mol%, about 0.1 mol% to about 7 mol%, about 0.1 mol% to about 6 mol%, about 0.1 mol% to about 5 mol%, about 0.1 mol% to about 4 mol%, about 1 mol% to about 7 mol%, about 2 mol% to about 6 mol%, or about 3 mol% to about 6 mol%, and all ranges and sub-ranges therebetween.
[0142] In one or more embodiments, the glass composition includes an amount of ZrO2 equal to or less than about 0.2 mol%, less than about 0.18 mol%, less than about 0.16 mol%, less than about 0.15 mol%, less than about 0.14 mol%, less than about 0.12 mol%. In one or more embodiments, the glass composition includes ZrO2 in a range from about 0.01 mol% to about 0.2 mol%, about 0.01 mol% to about 0.18 mol%, about 0.01 mol% to about 0.16 mol%, about 0.01 mol% to about 0.15 mol%, about 0.01 mol% to about 0.14 mol%, about 0.01 mol% to about 0.12 mol%, or about 0.01 mol% to about 0.10 mol%, and all ranges and sub-ranges therebetween.
[0143] In one or more embodiments, the glass composition includes SnO in an amount equal to or less than about 0.2 mol%, less than about 0.18 mol%, less than about 0.16 mol%, less than about 0.15 mol%, less than about 0.14 mol%, less than about 0.12 mol%. In one or more embodiments, the glass composition includes SnO in a range of about 0.01 mol% to about 0.2 mol%, about 0.01 mol% to about 0.18 mol%, about 0.01 mol% to about 0.16 mol%, about 0.01 mol% to about 0.15 mol%, about 0.01 mol% to about 0.14 mol%, about 0.01 mol% to about 0.12 mol%, or about 0.01 mol% to about 0.10 mol%, and all ranges and sub-ranges therebetween.
[0144] In one or more embodiments, the glass composition may include an oxide that imparts color or hue to the glass article. In some embodiments, the glass composition includes an oxide that prevents the glass article from discoloring when the glass article is exposed to ultraviolet radiation. Examples of such oxides include, but are not limited to, oxides of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Ce, W, and Mo.
[0145] In one or more embodiments, the glass composition includes Fe expressed as Fe2O3, wherein Fe is present in an amount up to (and including) about 1 mol%. In some embodiments, the composition is substantially free of Fe. In one or more embodiments, the glass composition includes Fe2O3 in an amount equal to or less than about 0.2 mol%, less than about 0.18 mol%, less than about 0.16 mol%, less than about 0.15 mol%, less than about 0.14 mol%, less than about 0.12 mol%. In one or more embodiments, the glass composition includes Fe2O3 in a range from about 0.01 mol% to about 0.2 mol%, about 0.01 mol% to about 0.18 mol%, about 0.01 mol% to about 0.16 mol%, about 0.01 mol% to about 0.15 mol%, about 0.01 mol% to about 0.14 mol%, about 0.01 mol% to about 0.12 mol%, or about 0.01 mol% to about 0.10 mol%, and all ranges and sub-ranges therebetween.
[0146] Where the glass composition includes TiO2, TiO2 may be present in an amount of about 5 mol% or less, about 2.5 mol% or less, about 2 mol% or less, or about 1 mol% or less. In one or more embodiments, the glass composition may be substantially free of TiO2.
[0147] Exemplary glass compositions include SiO2 in an amount ranging from about 65 mol% to about 75 mol%, Al2O3 in an amount ranging from about 8 mol% to about 14 mol%, Na2O in an amount ranging from about 12 mol% to about 17 mol%, K2O in an amount ranging from about 0 mol% to about 0.2 mol%, and MgO in an amount ranging from about 1.5 mol% to about 6 mol%. Optionally, SnO2 may be included in an amount otherwise disclosed herein.
[0148] Strengthened glass properties
[0149] In one or more embodiments, the glass substrate 52 discussed herein may be formed from a strengthened glass sheet or article. In one or more embodiments, the glass article used to form the layer(s) of the decorative glass structure discussed herein may be strengthened to include a compressive stress extending from the surface to a depth of compression (DOC). The compressive stress region is balanced by a central portion exhibiting tensile stress. At the DOC, the stress transitions from a positive (compressive) stress to a negative (tensile) stress.
[0150] In one or more embodiments, the glass articles used to form the layer(s) of the decorative glass structures discussed herein can be mechanically strengthened by exploiting the mismatch in thermal expansion coefficients between portions of the glass to produce regions of compressive stress and a central region exhibiting tensile stress. In some embodiments, the glass articles can be thermally strengthened by heating the glass to a temperature above the glass transition point and then rapidly quenching.
[0151] In one or more embodiments, the glass articles used to form the (multiple) layers of the decorative glass structures discussed herein may be chemically strengthened by ion exchange. In the ion exchange process, ions at or near the surface of the glass article are replaced or exchanged with larger ions of the same valence or oxidation state. In embodiments where the glass article comprises an alkali-aluminosilicate glass, the ions and larger ions in the surface layer of the article are monovalent alkali metal cations, such as Li+, Na+, K+, Rb+, and Cs+. Alternatively, the monovalent cations in the surface layer may be replaced with monovalent cations other than alkali metal cations, such as Ag+, etc. In such embodiments, the monovalent ions (or cations) exchanged into the glass article produce stress.
[0152] The ion exchange process is typically performed by immersing the glass article in a molten salt bath (or two or more molten salt baths) containing larger ions to be exchanged with smaller ions in the glass article. It should be noted that aqueous salt baths may also be utilized. In addition, the composition of the bath(s) may include more than one type of larger ion (e.g., Na+ and K+) or a single larger ion. Those skilled in the art will appreciate that the parameters for the ion exchange process, including but not limited to bath composition and temperature, immersion time, number of immersions of the glass article in one or more salt baths, use of multiple salt baths, additional steps (such as annealing, washing, etc.), are typically determined by the composition of the glass layer(s) of the decorative glass structure (including the structure of the article and any crystalline phases present) and the desired DOC and CS of the glass layer(s) of the decorative glass structure resulting from strengthening.
[0153] Exemplary molten bath compositions may include nitrates, sulfates, and chlorides of larger alkali metal ions. Typical nitrates include KNO3, NaNO3, LiNO3, NaSO4, and combinations thereof. The temperature of the molten salt bath is typically in the range of about 380°C to about 450°C, and the immersion time is in the range of about 15 minutes to about 100 hours, depending on the glass thickness, bath temperature, and glass (or monovalent ion) diffusivity. However, temperatures and immersion times different from those described above may also be used.
[0154] In one or more embodiments, the glass article used to form the (multiple) layers of decorative glass may be immersed in a molten salt bath having 100% NaNO3, 100% KNO3, or a combination of NaNO3 and KNO3 at a temperature of about 370°C to about 480°C. In some embodiments, the (multiple) glass layers of the decorative glass may be immersed in a molten mixed salt bath comprising about 5% to about 90% KNO3 and about 10% to about 95% NaNO3. In one or more embodiments, the glass article may be immersed in a second bath after being immersed in the first bath. The first bath and the second bath may have different compositions and / or temperatures from each other. The immersion time in the first bath and the second bath may vary. For example, the immersion in the first bath may be longer than the immersion in the second bath.
[0155] In one or more embodiments, the glass article used to form the layer(s) of the decorative glass structure may be immersed in a molten mixed salt bath including NaNO3 and KNO3 (e.g., 49% / 51%, 50% / 50%, 51% / 49%) at a temperature below about 420°C (e.g., about 400°C or about 380°C) for less than about 5 hours, or even about 4 hours or less.
[0156] The ion exchange conditions can be tailored to provide a "spike" or increase in the slope of the stress profile at or near the surface of the resulting glass layer(s) of the decorative glass structure. The spike may result in a larger surface CS value. Due to the unique properties of the glass compositions used in the glass layer(s) of the decorative glass structure described herein, this spike can be achieved by a single bath or multiple baths, where the bath(s) have a single composition or a mixed composition.
[0157] In one or more embodiments, when more than one univalent ion is exchanged into a glass article used to form the layer(s) of the decorative glass structure, different univalent ions may be exchanged to different depths within the glass layer (and produce different amounts of stress at different depths within the glass article). The resulting relative depths of the stress-producing ions may be determined and result in different characteristics of the stress profile.
[0158] CS is measured using means known in the art, such as by a surface stress meter (FSM), using commercially available instruments such as the FSM-6000 manufactured by Orihara Industrial Co., Ltd. (Japan). Surface stress measurements rely on accurate measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass. SOC is in turn measured by methods known in the art, such as the fiber method and the four-point bending method (both of which are described in ASTM standard C770-98 (2013) entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient", the contents of which are incorporated herein by reference in their entirety), and the block cylinder method. As used herein, CS may be the "maximum compressive stress", i.e., the highest compressive stress value measured within the compressive stress layer. In some embodiments, the maximum compressive stress is located at the surface of the glass article. In other embodiments, the maximum compressive stress may occur at a certain depth below the surface, giving the compression profile the appearance of a "buried peak".
[0159] Depending on the strengthening method and conditions, DOC can be measured by FSM or by a scattered light polariscope (SCALP) (such as the SCALP-04 scattered light polariscope available from GlasStress Ltd. located in Tallinn, Estonia). When the glass article is chemically strengthened by an ion exchange process, either FSM or SCALP can be used, depending on the ions exchanged into the glass article. When the stress in the glass article is caused by the exchange of potassium ions into the glass article, FSM is used to measure DOC. In the case where the stress is caused by the exchange of sodium ions into the glass article, SCALP is used to measure DOC. In the case where the stress in the glass article is caused by the exchange of potassium ions and sodium ions into the glass, DOC is measured by SCALP because it is believed that the exchange depth of sodium ions indicates the DOC, and the exchange depth of potassium ions indicates the change in the magnitude of compressive stress (but not the change of stress from compression to tension); the exchange depth of potassium ions in such glass articles is measured by FSM. Central tension or CT is the maximum tensile stress and is measured by SCALP.
[0160] In one or more embodiments, the glass article used to form the layer(s) of the decorative glass structure may be strengthened to exhibit a DOC described as a fraction of the thickness t of the glass article (as described herein). For example, in one or more embodiments, the DOC may be equal to or greater than about 0.05t, equal to or greater than about 0.1t, equal to or greater than about 0.11t, equal to or greater than about 0.12t, equal to or greater than about 0.13t, equal to or greater than about 0.14t, equal to or greater than about 0.15t, equal to or greater than about 0.16t, equal to or greater than about 0.17t, equal to or greater than about 0.18t, equal to or greater than about 0.19t, equal to or greater than about 0.2t, equal to or greater than about 0.21t. In some embodiments, the DOC may be in a range of about 0.08t to about 0.25t, about 0.09t to about 0.25t, about 0.18t to about 0.25t, about 0.11t to about 0.25t, about 0.12t to about 0.25t, about 0.13t to about 0.25t, about 0.14t to about 0.25t, about 0.15t to about 0.25t, about 0.08t to about 0.24t, about 0.08t to about 0.23t, about 0.08t to about 0.22t, about 0.08t to about 0.21t, about 0.08t to about 0.2t, about 0.08t to about 0.19t, about 0.08t to about 0.18t, about 0.08t to about 0.17t, about 0.08t to about 0.16t, or about 0.08t to about 0.15t. In some cases, the DOC may be about 20 μm or less. In one or more embodiments, the DOC may be about 40 μm or greater, for example, about 40 μm to about 300 μm, about 50 μm to about 300 μm, about 60 μm to about 300 μm, about 70 μm to about 300 μm, about 80 μm to about 300 μm, about 90 μm to about 300 μm, about 100 μm to about 300 μm, about 110 μm to about 300 μm, about 120 μm to about 300 μm, about 140 μm to about 300 μm, about 150 μm to about 300 μm, about 40 μm to about 290 μm, about 40 μm to about 280 μm. μm, about 40 μm to about 260 μm, about 40 μm to about 250 μm, about 40 μm to about 240 μm, about 40 μm to about 230 μm, about 40 μm to about 220 μm, about 40 μm to about 210 μm, about 40 μm to about 200 μm, about 40 μm to about 180 μm, about 40 μm to about 160 μm, about 40 μm to about 150 μm, about 40 μm to about 140 μm, about 40 μm to about 130 μm, about 40 μm to about 120 μm, about 40 μm to about 110 μm, or about 40 μm to about 100 μm.
[0161] In one or more embodiments, the glass article used to form the layer(s) of the decorative glass structure may have a CS (which may be found at the surface or at a depth within the glass article) of about 200 MPa or greater, 300 MPa or greater, 400 MPa or greater, about 500 MPa or greater, about 600 MPa or greater, about 700 MPa or greater, about 800 MPa or greater, about 900 MPa or greater, about 930 MPa or greater, about 1000 MPa or greater, or about 1050 MPa or greater.
[0162] In one or more embodiments, the glass article used to form the layer(s) of the decorative glass structure may have a maximum tensile stress or central tension (CT) of about 20 MPa or more, about 30 MPa or more, about 40 MPa or more, about 45 MPa or more, about 50 MPa or more, about 60 MPa or more, about 70 MPa or more, about 75 MPa or more, about 80 MPa or more, or about 85 MPa or more. In some embodiments, the maximum tensile stress or central tension (CT) may be in the range of about 40 MPa to about 100 MPa.
[0163] Unless explicitly stated otherwise, any method described herein is in no way intended to be construed as requiring that its steps be performed in a specific order. Thus, if a method claim does not actually recite the order in which its steps are to be followed, or if it is not otherwise specifically stated in the claims or specification that the steps are to be limited to a specific order, no specific order is intended to be inferred. In addition, as used herein, the article "a" is intended to include one or more than one component or element, and is not intended to be construed as meaning only one.
[0164] It will be apparent to those skilled in the art that various modifications and changes may be made without departing from the spirit or scope of the disclosed embodiments. Since modifications, combinations, sub-combinations, and changes of the disclosed embodiments that include the spirit and substance of the disclosed embodiments may be conceived by those skilled in the art, the disclosed embodiments should be interpreted as including all contents within the scope of the appended claims and their equivalents.
Claims
1. A glass product, comprising: a support structure, the support structure comprising a support surface; A glass substrate, the glass substrate comprising a first main surface and a second main surface, the second main surface being opposite to the first main surface; and an adhesive bead disposed between the support surface and the second major surface, wherein: The adhesive bead includes a plurality of outer surfaces extending between the support structure and the glass substrate, The plurality of outer surfaces extend at a first angle relative to the second major surface at a first edge thereof closest to the glass substrate, and Each of the first angles is greater than or equal to 35° and less than or equal to 60°.
2. The glass article of claim 1, wherein the plurality of outer surfaces extend at a second angle relative to the support surface at a second edge thereof closest to the support structure.
3. The glass article of claim 2, wherein for each of the plurality of exterior surfaces, the first angle is equal to the second angle.
4. The glass article of any one of claims 1-3, wherein each of the first angles is greater than or equal to 40° and less than or equal to 50°.
5. The glass article of any one of claims 1-4, wherein each of the first angles is greater than or equal to 42° and less than or equal to 48°.
6. The glass article of any one of claims 1-5, wherein each of the first angles is greater than or equal to 44° and less than or equal to 46°.
7. The glass article of any one of claims 1-6, wherein the support surface is curved and the adhesive beads hold the glass substrate in a curved configuration on the support surface when the glass substrate is cold formed.
8. The glass article of claim 7, wherein: As the glass substrate is cold formed, the adhesive bead is maintained in a tensile stress state. The location where the tensile stress in the adhesive bead comprises a maximum magnitude is displaced from the interface between the adhesive bead and the glass substrate and to the bulk of the adhesive bead.
9. The glass article of any one of claims 1-8, wherein the adhesive bead extends continuously around the perimeter of the glass substrate between the glass substrate and the support structure.
10. The glass article of any one of claims 1-8, wherein the glass article comprises a plurality of adhesive beads disposed along a bead path between the glass substrate and the support structure, each of the plurality of adhesive beads comprising a plurality of outer surfaces extending at a first angle relative to the second major surface, the first angle being greater than or equal to 35° and less than or equal to 60°.
11. The glass article of any one of claims 1-10, wherein the plurality of outer surfaces of the adhesive bead are concave such that the adhesive bead comprises a minimum cross-sectional dimension between the glass substrate and the support structure.
12. The glass article of claim 11, wherein each of the plurality of outer surfaces of the adhesive bead is continuously curved throughout the entire distance between the glass substrate and the support structure.
13. The glass article of any one of claims 1-12, wherein the adhesive beads comprise an elastic modulus of 0.1 MPa to 300 MPa in a cured state.
14. A glass product, comprising: a support structure comprising a curved support surface, the curved support surface being curved with a radius of curvature greater than or equal to 75 mm and less than or equal to 10,000 mm; A glass substrate, the glass substrate comprising a first main surface and a second main surface, the second main surface being opposite to the first main surface; and an adhesive bead disposed between the curved support surface and the second major surface and holding the glass substrate in a curved shape on the curved support surface, wherein: The glass substrate is cold formed so that stress exists in the adhesive bead, The adhesive bead includes a plurality of outer surfaces extending between the support structure and the glass substrate, The plurality of outer surfaces extend at a first angle relative to the second major surface at a first edge thereof closest to the glass substrate, and Each of the first angles is greater than or equal to 35° and less than or equal to 60°, so that a position where the stress in the adhesive bead is at a maximum value is displaced from an interface between the glass substrate and the adhesive bead.
15. The glass article of claim 14, wherein the plurality of outer surfaces extend at a second angle relative to the support surface at a second edge thereof closest to the support structure.
16. The glass article of claim 15, wherein for each of the plurality of exterior surfaces, the first angle is equal to the second angle.
17. The glass article of any one of claims 14-16, wherein each of the first angles is greater than or equal to 40° and less than or equal to 50°.
18. The glass article of any one of claims 14-17, wherein each of the first angles is greater than or equal to 44° and less than or equal to 46°.
19. The glass article of any one of claims 14-18, wherein the adhesive bead extends continuously around the perimeter of the glass substrate between the glass substrate and the support structure.
20. The glass article of any one of claims 14-18, wherein the glass article comprises a plurality of adhesive beads disposed along a bead path between the glass substrate and the support structure, each of the plurality of adhesive beads comprising a plurality of outer surfaces extending at a first angle relative to the second major surface, the first angle being greater than or equal to 35° and less than or equal to 60°.
21. The glass article of any one of claims 14-20, wherein the plurality of outer surfaces of the adhesive bead are concave such that the adhesive bead comprises a minimum cross-sectional dimension between the glass substrate and the support structure.
22. The glass article of any one of claims 14-21, wherein: The adhesive beads comprise an elastic modulus in the cured state of 0.1 MPa to 300 MPa, and The support structure is composed of one of aluminum and stainless steel.
23. A method of attaching a glass substrate to a support structure, the method comprising: dispensing the adhesive bead onto one of the glass substrate and the support structure while the adhesive of the adhesive bead is in an uncured state; contacting the adhesive bead with a plurality of shaping members to shape an outer surface of the adhesive bead so that the outer surface of the adhesive bead extends at an angle relative to the one of the glass substrate and the support structure at an edge of the outer surface, the angle being greater than or equal to 35° and less than or equal to 60°; contacting the plurality of shaping members with the other of the glass substrate and the support structure such that after shaping, the adhesive bead contacts both the support structure and the glass substrate; and The adhesive is cured to solidify the adhesive beads, so that the glass substrate and the support structure are bonded to each other through the adhesive beads.
24. The method of claim 23, wherein contacting the adhesive bead with the plurality of shaping members comprises: The plurality of shaping members are moved into contact with the adhesive bead after dispensing the adhesive bead.
25. The method of claim 24, wherein the plurality of shaping members are moved to contact the adhesive beads by placing the plurality of shaping members between the glass substrate and the support structure such that the shaping members are in contact with the glass substrate and the support structure.
26. The method of claim 23, wherein contacting the adhesive bead with the plurality of shaping members comprises: The adhesive is dispensed into an adhesive shaping cavity defined by a plurality of sacrificial shaping members disposed on the one of the glass substrate and the support structure.
27. The method of claim 26, further comprising: The plurality of sacrificial shaping members are removed after the curing of the adhesive such that the adhesive bead retains a shape determined by the plurality of sacrificial shaping members.
28. The method of claim 27, wherein the plurality of sacrificial plastic members are formed of a wax material, and removing the plurality of sacrificial plastic members comprises heating the plurality of sacrificial plastic members to a temperature less than or equal to 70°C.
29. The method of any one of claims 23-28, further comprising: The glass substrate is cold formed by applying a bending force to the glass substrate prior to depositing the adhesive.
30. The method of claim 29, wherein the adhesive is dispensed on the glass substrate after cold forming, and after the adhesive is cured, the adhesive bead holds the glass substrate in a cold formed state such that bending stress exists in the adhesive bead.
31. The method of any one of claims 23-30, wherein the outer surface of the adhesive bead extends at an angle greater than or equal to 35° and less than or equal to 60° at its edge relative to both the glass substrate and the support structure due to being contacted by the plurality of shaping members.
Citation Information
Patent Citations
Curved glass constructions and methods for forming same
US11772361B2